Árboles de Navidad: Estado de la Reforestación en Costa Rica - Torres-Córdoba, Gustavo; Carvajal-Venegas, Dorian (Instituto Tecnológico de Costa Rica, 2012)
The cultivation of Christmas trees practiced in Costa Rica is unique in its style in Tropical America, because this has been based on the exclusive use of cypress (Cupressus lusitanica) in a ratio of supply and demand and negligible positive for producers. This type of reforestation is unique in that trees receive special care from the time of planting to harvest, making intensive character. But the forestry sector has actual and accurate documentation of the geographical location of these plantations, as well as techniques or practices used by farmers in reforestation, and also on issues related to its marketing and commercialization. This activity strengthening research main objective was to assess the state of the Christmas tree reforestation in Costa Rica. This type of reforestation has a potential close to a crash as long as aspects outweigh line aimed at ensuring better forest management silvicultural technical assistance. The experience of the producer, the existence of a technology package and a tradition by the user are opportunities that favor this practice in our country.
Proyecto de Investigación. Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2012.
Keywords: Silvicultura; Especies; Requerimientos; Trazado; Plantaciones forestales